A Business Communication Assessment Tool Based on Workplace Assessment Processes and Service-Learning. Issue 2 (June 2021) - Sharma, Daneshwar
The instructor developed an assessment tool based on Service-Learning (S-L) for developing business and professional communication (BPC) skills in business school students in India ( N = 117). The students practiced their organizational, leadership, and interpersonal communication skills in an authentic, contextual, and workplace atmosphere during this S-L assessment project. The effectiveness of the assessment tool has been studied with a posttest and then pretest. The need for an innovative and holistic BPC skills assessment tool is discussed. The article also presents implications of the project for students and pedagogy along with the challenges in using the assessment project.